2013
DOI: 10.1093/aje/kwt309
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Outcome Misclassification in Estimates of the Effect of Occupational Asbestos Exposure on Lung Cancer Death

Abstract: In studies of the health effects of asbestos, lung cancer death is subject to misclassification. We used modified maximum likelihood to explore the effects of outcome misclassification on the rate ratio of lung cancer death per 100 fiber-years per milliliter of cumulative asbestos exposure in a cohort study of textile workers in Charleston, South Carolina, followed from 1940 to 2001. The standard covariate-adjusted estimate of the rate ratio was 1.94 (95% confidence interval: 1.55, 2.44), and modified maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Likewise, a more stringent case definition cut-point set at severe periodontitis, which equates to decreasing sensitivity, also resulted in PRP estimates that were biased in terms of magnitude and direction for each of the PRPs we investigated. Given changes in specificities tend to have a much larger impact on effect estimates than changes in sensitivi-ties (Copeland et al 1977, Lyles et al 2011, Edwards et al 2014, the magnitude of bias that we observed were not so severe.…”
Section: Discussionmentioning
confidence: 64%
“…Likewise, a more stringent case definition cut-point set at severe periodontitis, which equates to decreasing sensitivity, also resulted in PRP estimates that were biased in terms of magnitude and direction for each of the PRPs we investigated. Given changes in specificities tend to have a much larger impact on effect estimates than changes in sensitivi-ties (Copeland et al 1977, Lyles et al 2011, Edwards et al 2014, the magnitude of bias that we observed were not so severe.…”
Section: Discussionmentioning
confidence: 64%
“…This method would be suitable for analyses in which follow-up time varies between individuals (for estimating rates rather than risks) and the hazard is approximately constant. Edwards et al 2014 provide sample SAS code for this method [51•]. …”
Section: Quantifying Impact and Adjusting Estimatesmentioning
confidence: 99%
“…In this section we introduce the model of interest using an example from Edwards et al [ 13 ]. To aid in the description, we build the model with increasing levels of complexity communicated through the language of directed graphical models, also called Bayesian networks.…”
Section: The Modelmentioning
confidence: 99%
“…In other words, accounting for misclassification with the two parameters of sensitivity and specificity overparameterizes the model in a way that demands to be addressed. Edwards et al [ 13 ] consider and known and provide a method to obtain the maximum likelihood estimators (MLEs) while Stamey et al [ 9 ] assume information about and exist not as point estimates but rather in the form of probability distributions with which one can perform a Bayesian analysis, i.e ., prior distributions. Here, we investigate both the fixed and unknown approaches via the Bayesian paradigm.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation